Carbon absorption by forests in the Volga region and Siberia: state and prospects - A. I. Pyzhev; E. A. Vaganov (Georesursy, 2024)
The prospect of Russia’s economic development will be inextricably bound up with the country’s success in the implementation of global climate initiatives. The strategy for the development of the national economy with a low level of greenhouse gas emissions, which is currently being formed, implies the fullest use of the potential for carbon sequestration by forest ecosystems, including through the implementation of various forest-climatic projects.The article shows that despite the world’s largest forest areas, the carbon-absorbing capacity of Russian forests cannot balance anthropogenic greenhouse gas emissions. Using the examples of several regions of the Volga region and Siberia, the spatial dynamics of the forest carbon budget in the 2010s is considered. For the regions of Siberia rich in boreal forests, there is a significant disproportion between the quantitative and qualitative characteristics of forest resources and the absorbing capacity, which is explained by the ineffective forestry regime in the territory and the high intensity of forest disturbances. Taking into account the fact that building an effective system for combating forest fires and insect pests requires very voluminous and expensive measures, the effectiveness of which is difficult to assess, the above illustrations of the current situation lead to the idea that, in addition to using the potential for increasing carbon sequestration in traditional forest regions in the implementation of forest-climatic projects should pay attention to sparsely forested areas.